The Effect Of Waist Flexibility Training On Smashing Ability In Extracurricular Volleyball Games SMA Negeri 10 Kota Bengkulu - Ramadona, Fito; Ertanto, Dody; Perdima, Feby Elra (Universitas Dehasen Bengkulu, 2026)
This study aimed to determine the effect of waist flexibility training on smashing ability in extracurricular volleyball games at State Senior High School 10, Bengkulu City. A total sampling method was used to determine the number of respondents, resulting in 16 respondents participating in the extracurricular volleyball games at State Senior High School 10, Bengkulu City. This experimental study employed a One Group Pretest-Posttest design, a pre-experimental design consisting of a pretest (test before treatment) and a posttest (test after treatment) within one group. Data collection used test scores. Descriptive data analysis techniques and t-tests were used. The results of this study indicate an effect of waist flexibility training on smashing ability in extracurricular volleyball games at State Senior High School 10, Bengkulu City, with a calculated t-value of 3.437 and a t-table value of 1.753, with a significance level of α = 0.05 and df = 16.